The Concept of Socially Inclusive Library in Changing Society - Kulikauskienė, Kristina (Socialiniai tyrimai, 2019)
In today’s world, organizations face constant and various changes, such as new technologies, new markets, changing legal and regulatory frameworks, internal organizational changes, and changes in customer’s needs (Butt, Nawab, Zahid 2018). As public sector organizations, public libraries also face changes and the need for change. Modern society expects libraries to have access to information, to offer cultural and lifelong learning activities, and to contribute in reducing informational, digital and social exclusion. In order to meet the changing needs of society, public libraries are expanding their roles from book supply places to community centers, offering lifelong learning activities, free access to information resources, cultural and information events as well as leisure and spaces for social interaction. Therefore, defining the concept of an inclusive library can, on the one hand, broaden the concept of an inclusive organization and, on the other hand, contribute to improving the quality of library services in order to reduce social exclusion in communities and society in general. Applying the analytical content analysis of theoretical sources and scientific literature on the main features of an inclusive organization, the article aims to define the essential features of a socially inclusive library as a public organization and to analyse the concept of an inclusive library.One of the main goals of organizational change today is to achieve social responsibility and maximize sustainability. Social responsibility in organizations means meeting the needs of stakeholders and the sustainable development of the organization (Mory et al. 2016). In the context of social responsibility, the concept of organizational inclusion emerges. An inclusive organization is a modern organization. Such organization is based on its internal resources and must constantly increase its potential, improve all activities, develop plans to achieve these activities, in other words, it must evolve and be a constantly developing organization (Zakarevicius, 2012). The analysis of the scientific literature suggests, that the definition of inclusive organization in the context of public organizations is widening – from focusing on employee inclusion to a concern for the well-being of all society in general, especially for those, experiencing social exclusion.Today, being public sector organizations, libraries are in the state of constant change. Libraries are influenced by innovations which require changes in their activities (Carrillo, Gregory, 2019). At the same time, society’s expectations for libraries are changing – libraries are becoming community centers, creating and sharing knowledge, and at the same time carrying out traditional bookkeeping and publishing activities (Irwin, Silk, 2019). The following roles of the public libraries are offered in the scientific literature: informational, educational cultural, communal and social role. In the context of changing library roles, the need for the library to become a socially responsible and inclusive organization is emphasized. All public organizations, including public libraries, are required to be accountable for how their services contribute to the well-being of society (Racelis, 2018). Applying the analytical content analysis of theoretical sources, the concept of the inclusive library is defined – the inclusive library is accessible to all members of different social groups in society, inclusive library cares for its employees, develops their competencies, meets customer’s needs, and involves all members of the community it serves. The concept of inclusive library, unlike other inclusive public organizations, emphasizes not only the need to respond to the needs of stakeholders (which is common to all inclusive organizations), but also emphasizes a wide variety of stakeholders and their needs that are not always easily predicted. Library customers include people of all ages and social backgrounds, from children to older people. In addition, libraries can constantly expand their partner network and engage them in activities by collaborating with other formal and informal organizations of the community, that are interested in engaging people in learning, employment, etc. Another important aspect is that the inclusive library must constantly focus on the quality, diversity, accessibility and competencies of its staff, as library staff competencies are essential in ensuring quality of library services.To sum up, it is important to mention, that the changing roles of libraries and the constant desire to respond to and meet the needs of different groups of society members, determine the need for libraries to become socially responsible and inclusive organizations. All public organizations, as well as public libraries, are required to take responsibility for the public good and the delivery of social services to the public. This encourages libraries to change and to become inclusive organizations themselves. By implementing and effectively managing the process of change, libraries can become socially inclusive – libraries whose services are accessible to members of all different social groups in society, which care about the well-being of their employees, meet a customer’s needs, and engage community and serve various people. These features distinguish libraries from other public organizations. Public libraries, being community centers, can provide equal access to cultural, informational, lifelong learning activities, self-education events, and meaningful leisure activities for all people. In this way, the inclusive library creates extra value for society and contributes to social justice. Public libraries can act as social justice executors, providing all members of the society with access to resources of information, enabling them to participate in educational and cultural activities and events. The extensive network, the variety of free services and the availability of these services enable libraries to become community centers – places where people gather to learn, participate in events, and spend their free time.
Keywords: inclusive organization; changing library roles; satisfaction of society needs